Teacher Knowledge on Student and Its Relation with Teching and Learning Process - Noh, Mohd Aderi Che (European Journal of Social Science Education and Research, 2023)
Knowledge on students is needed for teachers so that they can provide the appropriate teaching and learning that meet the needs of every student as they come with differing backgrounds and culture. These differences should be noted to ensure that the strategies, approaches, methods and techniques selected are able to represent all ethnic groups in the class. Therefore, this study explores teachers' knowledge on students, especially the socio-economic and socio-cultural aspects of students. Qualitative research design was used in this case study which involved four teachers of Islamic education in Sarawak via purposive sampling. Data were analyzed thematically using the Atlas. ti7. 1. 7software. The results showed participants in the study have the initiative to find out the background of the students, especially the economic and cultural aspects of students. Knowledge about both these aspects helps them in conveying the teaching of Islam. The results also indicate that the socio-economic and family culture can have positive and negative implications for the students' learning processes in the classroom. Hopefully, these findings provide a paradigm shift for teachers of Islamic education in creating meaningful lessons for students.
Keywords: knowledge on students, cultural diversity, Islamic education, socio-economic, socio-cultural